Pulsed ultrasound-assisted extraction of pomegranate (Punica granatum L. var. Malas) peel for production of value-added parboiled wheat noodles - Kazemi, Milad (2015)
In the current study, an attempt was made to improve the functional properties of parboiled wheat noodles by using pomegranate (Punica granatum L. var. Malas) peel extracts. Pomegranate peel is known to be rich in bioactive compounds including phenolic compounds that are beneficial for human health. Although pomegranate peel contains a notable content of phenolic compounds, it is not currently being utilized commercially and simply thrown away as waste or used for feeding of cattle (521 kg/ ton). On the other hand, noodles are one of the popular foods in the Asian region because of their low cost, ease of preparation, palatable taste and being a rich source of carbohydrate. However, they lack in functional properties. Therefore, extracting the polyphenols from the pomegranate peel using new extraction techniques such as pulsed ultrasound-assisted extraction (PUAE) and incorporating them into wheat noodles not only improve the functional properties of the noodles but also will add value to the by-product of the pomegranate industry. Moreover, applying PUAE can improve the shortcomings related to the conventional extraction methods such as time and energy consumption, low efficiency and relatively high solvents consumption. Since no study has been done on the optimization of PUAE from pomegranate peel of the Malas variety, this study is undertaken with the following objectives: (i) to optimize the operating conditions of pulsed ultrasound-assisted extraction (PUAE) for obtaining the highest yield of crude extract with the maximum antioxidant properties from pomegranate peel, and (ii) to determine the effect of incorporation of pomegranate peel extract (PPE) on the physicochemical and textural properties, and microstructural and sensory characteristics of white salted and yellow alkaline noodles. In the first part of the study, the effects of three extraction variables including extraction time (min), duty cycle (%) and intensity level (W/cm2 ) on the yield of crude extract, total phenolic content (TPC), DPPH free radical scavenging activity, ferric reducing antioxidant power (FRAP), punicalagin, ellagic acid (EA) and gallic acid (GA) contents, and chroma (color saturation) of PPE were investigated using response surface methodology in an attempt to find the optimum PUAE condition. The results revealed that all the ultrasound variables except for duty cycle significantly (p ≤ 0.05) affected the antioxidant activity and phenolic content of the crude extract from pomegranate peel. Among the extraction variables studied, the extraction time was the most significant (p ≤ 0.05) variable which positively affected all the response variables. The intensity level of ultrasonic waves also had positive significant (p ≤ 0.05) effect on the majority of the response variables except for FRAP. Based on the observation, the highest and lowest extraction yields were 41.63% and 26.82%, respectively. The results showed that TPC of the crude extract varied from 273.05 to 320.26 mg GA equivalent/g of dry weight extract. The FRAP ranged from 6.21 to 7.17 mmol Fe2+/ g dry weight and DPPH free radical scavenging activity (IC50) of the crude extract varied from 220.25 μg/ml to 266.74 μg/ml depending on the extraction conditions. The quantities of punicalagin, EA and GA varied from 128.02 to 146.61 mg punicalagin/g dry weight, 10.12 to 22.53 mg EA/g dry weight and 2.60 to 5.11 mg GA/100 g dry weight, respectively. The current study demonstrated that the optimum extract was achieved by extraction for 10 min using 50% duty cycle and intensity level of 105 W/cm2 . The desirable extraction yield (41.14 %), TPC (318.71 mg GAE/g), DPPH free radical scavenging activity (220.03 µg/ml), FRAP (7.02 mmol FeSO4/g), punicalagin content (146.58 mg/g), EA content (20.66 mg/g), GA content (5.34 mg/100g) and the chroma (32.84) were obtained under the optimum extraction conditions. Therefore, the optimization of PUAE conditions led to obtaining high yield of the crude extract with the highest antioxidant activity in a very short extraction time (i.e. 10 min). In the second part of the work, a full factorial design was applied to investigate the effects of different concentrations of the pomegranate peel extract (0%, 0.75%, and 1.50%) and the noodle type (white salted and yellow alkaline wheat noodles) on the antioxidant activity (TPC, DPPH, and FRAP), physicochemical properties (color, pH and cooking quality), textural properties (firmness, adhesiveness, springiness, cohesiveness, gumminess, chewiness, and resilience), microstructural features and sensory characteristics of the noodles. The results indicated that the optimum cooking time of fortified white salted noodles (WSN) was shorter than yellow alkaline noodles (YAN). Percentages of cooking losses were within the acceptable range i.e. from 4.44% to 6.04%. The addition of pomegranate peel extract (PPE) to the noodle formulation did not significantly (p > 0.05) affect the cooking yield of wheat noodles; even though it led to a reduction in pH of noodles. The total phenolic contents, DPPH radical scavenging activity, and FRAP values varied from 4.07 to 8.61 mg GAE/g, 23.20 to 95.16% and 32.56 to 114.48 µmol FeSO4/g, respectively. The fortified white salted and yellow alkaline noodles showed significant (p ≤ 0.05) differences in color and textural properties. The fortified white salted noodles tend to have a softer texture, whereas the fortified yellow alkaline noodles were substantially harder compared to the control YAN. Microstructural observation using scanning electron microscopy (SEM) revealed that the fortified noodles had a more homogeneous and compact microstructure. Based on hedonic test, no significant difference (p > 0.05) was observed in the overall acceptability of these products with average scores ranging from 5.72 to 6.45; indicating that the degree of liking of panelists was between slightly like to moderately like. Thus, it can be concluded that the addition of pomegranate peel extract to the parboiled wheat noodles could improve their antioxidant properties without affecting the taste and overall acceptability of the noodles.